A new three-dimensional zinc(ii) metal–organic framework as a fluorescence sensor for sensing the biomarker 3-nitrotyrosine. Issue 30 (12th July 2022) - Geng, Jun; Li, Yuyao; Lin, Hongyan; Liu, Qianqian; Lu, Junjun; Wang, Xiuli
Abstract : A new 3D zinc-based metal–organic framework was successfully prepared, which exhibits excellent luminescence sensing performance toward the biomarker 3-nitrotyrosine with a high K SV, low detection limit and rapid response time. Abstract : 3-Nitrotyrosine (3-NT), an oxidative stress biomarker, is closely associated with various diseases. Thus, rapid and sensitive detection of 3-NT is of great significance for preventing and treating diseases. Herein, we reported a new 3D zinc-based metal–organic framework (Zn-MOF) [Zn(L)(HBTC)] (L = ( E )-4, 4′-(ethene-1, 2-diyl)bis[( N -pyridin-3-yl)benzamide], H3 BTC = 1, 3, 5-benzenetricarboxylic acid), which was structurally characterized by single crystal X-ray diffraction, IR, PXRD and TG. The Zn-MOF can be used as a highly efficient fluorescence sensing material to provide a direct and low-cost method for the rapid detection of 3-NT and shows high sensitivity with a K SV value of 6.596 × 10 4 M −1, a rapid luminescence response within 24 s, excellent selectivity, high anti-interference ability and good recyclability. It is the first example of a MOF being used to directly detect 3-NT as a luminescence sensor to our knowledge. The sensing mechanism of the Zn-MOF towards 3-NT is discussed in detail, which provides a basis for the rational design of MOF sensing materials and their application in biomarker detection.